Anatomical Variants of the Sciatic Nerve Division in the Pelvis, the Gluteal Region and the Thigh: A Cadaveric Study - Azza I Farag; Rasha M Salama (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Anatomical dissimilarities can be found in any part of the body and is pertinent to identify patients who are not treated successfully with standard medical care. Anatomical variants of the Sciatic Nerve (SN) were defined many years ago, and may have consequences in certain diseases, as sciatica. Specialised care may be required to these patients due to their unique anatomy. Aim: To study the cadaveric anatomical variants of the SN divisions in the pelvis, the gluteal region and the thigh and also to describe its linkage to the Piriformis Muscle (PM). Materials and Methods: This descriptive study was conducted from June 2021 to September 2021 in the Department of Anatomy of Qassim University, Saudi Arabia. Total 30 lower limbs and gluteal regions of formalin fixed male cadavers were used to study the anatomical variants of the SN division into its terminal branches and its relation to the PM. Numbers and percentages of the specimens falling in the groups were calculated and tabulated. Results: Out of 30, 3 specimens (10%), showed division of the SN in the pelvis, where both Tibial Nerve (TN) and Common Fibular Nerve (CFN) course separately below the piriformis muscle. While, 8 specimens (26.66%) showed division of the SN in the pelvis, where CFN pierces the piriformis muscle, and tibial nerve lies below it. About 5 specimens (16.66%), showed division of the sciatic nerve into tibial nerve and CFN in the gluteal region at the level of the obturator internus muscle. Additionally, 9 specimens (30%) showed division of the sciatic nerve into tibial nerve and CFN occurred in the upper of the posterior aspect of the thigh. Lastly, 5 specimens (16.66%), revealed division of the sciatic nerve into tibial nerve and CFN in the middle of the posterior aspect of the thigh. Conclusion: The most prevalent level of bifurcation of the SN in the present study was the upper part of the posterior aspect of the thigh (30%), while the least common level of the SN bifurcation was in the pelvis, before its exits in the gluteal region, where TN and CFN course separately below PM (10%).